Effect of High Frequency Transcranial Magnetic Stimulation (TMS) on Extensor Digitorum Communis Muscle Strength in Ischemic Stroke Patients - Juatmadja, Bastianus Alfian; Andriana, Meisy; Satyawati, Rwahita (Surabaya Physical Medicine and Rehabilitation Journal, 2020)
Abstract Background: Stroke may disrupt a patient's motor function, consequently affecting the quality of life. A stroke surviving brain has the ability to repair itself through neuroplasticity mechanism. Transcranial Magnetic Stimulation (TMS) is a non-invasive device which can be used to stimulate the lesioned part of the brain in hope of triggering neuroplasticity.Aims: To find prove of the repetitive Transcranial Magnetic Stimulation (rTMS) effect on extensor digitorum communis muscle strength improvement in ischemic stroke patients.Methods: Subjects suitable with the inclusion criteria (N=18) were divided into two groups,  control group and intervention group. The control group underwent conventional therapy exclusively every day for 5 days in a row, while the intervention group underwent rTMS therapy and conventional therapy every day for 5 days in a row. Extensor digitorum communis muscle strength was measured using surface electromyography (sEMG) before and after treatment.Result: Significant increase of sEMG numbers were found on control group (p=0,003) and intervention group (p=0,001). The increase from the intervention group was not different when compared to the control group (p=0,067).Conclusion: TMS can increase extensor digitorum communis muscle strength but with no difference with a conventional therapy.